Autosomal, mtDNA, and Y-Chromosome Diversity in Amerinds : Pre- and Post-Columbian Patterns of Gene Flow in South America (2000)
ABSTRACT: To evaluate sex-specific differences in gene flow between Native American populations from South America and between those populations and recent immigrants to the New World, we examined the genetic diversity at uni and biparental genetic markers of five Native American populations from Colombia and in published surveys from native South Americans. The Colombian populations were typed for five polymorphisms in mtDNA, five restriction sites in the b-globin gene cluster, the DQA1 gene, and nine autosomal microsatellites. Elsewhere, we published results for seven Y-chromosome microsatellites in the same populations. Autosomal polymorphisms showed a mean GST of 6.8%, in agreement with extensive classical marker studies of South American populations. MtDNA and Y-chromosome markers resulted in GST values of 0.18 and 0.165, respectively. When only Y chromosomes of confirmed Amerind origin were used in the calculations (as defined by the presence of allele T at locus DYS199), GST increased to 0.22. GST values calculated from published data for other South American natives were 0.3 and 0.29 for mtDNA and Amerind Y chromosomes, respectively. The concordance of these estimates does not support an important difference in migration rates between the sexes throughout the history of South Amerinds. Admixture analysis of the Colombian populations suggests an asymmetric pattern of mating involving mostly immigrant men and native women.